التجارة العربية البينية وسبل مواجهة معوقاتها - حمد الفارسي, أ.د.عيسى (Scientific Journal of University of Benghazi, 2026)
The inter - Arab trade is one of the most important topics of Arab economic integration. And despite the face that the proportion of inter-Arab trade, except of the oil, did not exceed 10% of the total external trade of Arab States until the beginnings of the twentieth century although, the inter - Arab trade is the basic motivation for a strong integration of Arab States which they seek to achieve. Therefore, the study recommends eliminating all obstacles, especially non-tariff restrictions, the provision and development of the means of transportation and diversify production structures among Arab countries so as to achieve the desired integration.